A comparison of collection development policies of selected university libraries - Santos, Kristine Marie P.; Faderon, Rosalie B. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The Philippine boasts of being the only Christian nation in Asia. In addition to the Christian majority, there is a vigorous 4 percent Muslim minority, concentrated in the southern islands of Mindanao, Sulu, and Palawan, scattered in isolated mountainous regions and the remaining 2 percent non-Western, indigenous beliefs and practices of those (Miller, 1996).A variety of sects like the Roman Catholic, Muslims, Protestants and the fundamentalist Christian groups, such as Jehovah's Witnesses and the Seventh Day Adventists, the Iglesia ni Kristo and Rizalists have emerged. As a result to these, these various religions established numerous colleges and universities. To name a few: for the Catholics, University of Sto. Tomas, Ateneo de Manila University, San Beda College, Holy spirit, etc.; for the protestants, Philippine Christian University, Trinity College and Silliman University, etc.; for the Iglesia ni Kristo, the New Era University.
This study aims to compare the collection development policies of selected sectarian university libraries, namely: New Era University, Diliman which is run by Iglesia ni Kristo; Ateneo de Manila University, Quezon city, which is Roman Catholic; and Philippine Christian University, which is protestant, to determine if the religion of the founder of each university affects the collection development policy of its respective library.
The study used the descriptive method of research and documentary analysis. The three selected sectarian universities (Ateneo De Manila University, New Era University, and the Philippine Christian University) value their respective religious affiliations in drafting the collection development policy to a certain extent. Rizal Library of the Ateneo de Manila University and New Era University have six elements comprising the policy statements. These include a) the user community (profile and their information needs); b) collection goal c) selection responsibility and criteria; d) collection evaluation and assessment; and e) weeding. On the other hand, Philippine Christian University has only five elements comprising the policy statement. These include a) users of the library; b) collection goal; c) policies in procurement of books; d) policies on payment; and e) procedure on payment. The above mentioned elements of the ADMU CD Policy and New Era University adhere to the elements given by Evans while the PCU Library CD Policy does not adhere to the elements given by Evans.
The researcher recommends the following measures: the need to describe and define clearly in the CD policy the key person who will decide on the religious morality of the library materials to be selected and acquired; define in the CD policy the weight of the religious affiliation of the three selected sectarian university libraries; the need for the three selected sectarian libraries to review and update their respective CD policies; the need to consult their respective library community or library users before drafting a CD policy; the addition of certain elements need in their CD policies; statements on gifts and censorship and levels of increasing intensity in the various subject areas included in their library collection; and the separation of CD policies from procedural manual.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Collection development (Libraries) -- Policy statements -- Philippines; Academic libraries -- Collection development. -- Philippines